The Role of Anti-Bullying Change Agents in Shaping Civic Dispositions to Tackle Bullying Behavior - Aris Suhendar; Muhammad Halimi (Proceeding International Conference on Religion, Science and Education, 2023)
Bullying is a habit that often occurs today in the world of education, this habit has often occurred over the past ten years in Indonesia. This bullying occurs due to several factors, such as the family environment, school environment, and also social environment in the community. Bullying that occurs in Indonesia today is often a culture in the name of seniority, until now it still always occurs in the environment of students. Bullying is also often done against peers who are perceived as weaker than him to get some pleasure. As a bullying prevention measure, Kemendikbud risk in collaboration with UNICEF Indonesia in 2017 has created the ROOTS program as a pilot program that concentrates on the role of students as agents of anti-bullying change in schools ranging from junior high school, high school, and vocational schools that have been selected as driving schools. The results of the National Assessment of the Ministry of Education and Culture of Research and Technology in 2021 stated that 24.4% of students in the Education unit experienced bullying in the past year. These anti-bullying change agents consist of 30 people from various classes and are handpicked by their schoolmates. The establishment of this bullying agency has a positive effect on the driving schools that already have and implement an anti-bullying change agent program, namely, (i) spreading messages and good behavior towards friends in the school environment, (ii) being an example of peers in school, (iii) reducing the impact of bullying that occurs in schools, (iv) providing exemplary examples of schools in the vicinity. This research uses literature review research which consists of three stages, namely identifying, analyzing, and evaluating problems. The results obtained from this study are that anti-bullying agents can change and form a good disposition for students to reduce the level of bullying that occurs in the school environment.